Endoscopic surveillance at 3 years after diagnosis, according to European guidelines, seems safe in patients with atrophic gastritis in a low-risk region. Issue 4 (April 2021) - Esposito, Gianluca; Dilaghi, Emanuele; Cazzato, Maria; Pilozzi, Emanuela; Conti, Laura; Carabotti, Marilia; Di Giulio, Emilio; Annibale, Bruno; Lahner, Edith
Abstract: Background: Autoimmune and multifocal atrophic gastritis (AG) are at risk for gastric neoplastic lesions. European guidelines recommend surveillance with high-quality endoscopy every 3 years. Aim: To prospectively investigate the occurrence of gastric neoplastic lesions at the 3-year follow-up in patients with autoimmune and multifocal AG. Methods: Longitudinal cohort study conducted between 2011 and 2019: consecutive patients with histological diagnosis of autoimmune or multifocal AG underwent follow-up gastroscopy 3 years after diagnosis with high-resolution-narrow-band-imaging endoscopes. Results: Overall, 160 patients were included(F117(73.0%);median age 66(35–87)years). Autoimmune and multifocal AG were present in 122(76.3%) and 38(23.7%) patients, respectively. At the 3-year follow-up, 16(10.0%) patients presented 16 gastric neoplastic lesions: 3(18.7%) gastric cancers, 4(25.0%) low-grade dysplasia, 2(12.5%) low-grade dysplasia adenomas, 7(43.7%) type-1 neuroendocrine tumours. In these patients, OLGA and OLGIM III/IV stages were present in 4(25.0)% and 1(6.3%), respectively; 11(69.0%) presented autoimmune AG, and all but one(93.7%) had parietal cells antibodies positivity ( p  = 0.026 vs patients without lesions). All lesions were endoscopically(87.5%) or surgically(12.5%) treated with favourable outcome. Age>70 years was associated with a 9-fold higher probability of developing gastric epithelial neoplastic lesions (OR 9.6, 95CI% 1.2–79.4, p  = 0.0359). Conclusions: The first endoscopic surveillance 3 years after diagnosis seems safe for autoimmune and multifocal AG patients and should be offered to elderly patients who are at higher risk for gastric neoplasia.